Pyogenic and fungal liver abscess with pneumonia due to abdominal trauma in pediatric: A rare case report - Dian , S Yova Yurisqi; Jaya, Septian Perdana Indra; Maharani, Annisa Dewi; Puspita, Eka Ari; Lemuel, Agung Budi (Indian Journal of Case Reports, 2025)
Liver abscess is an infection characterized by the presence of pus in the hepatic parenchyma due to necrosis caused by bacteria, fungi, or parasites. The prevalence of liver abscesses in children remains a significant issue in developing countries. We report a unique case of pediatric liver abscess, in which the primary etiology is suspected to be a blunt abdominal trauma that occurred a month prior. A 14-year-old boy presented with fever, shortness of breath, cough, and persistent right upper abdominal pain that had not improved despite a week of hospitalization. Diagnostic investigations revealed pneumonia, empyema, and a right lobe liver abscess. The patient’s condition progressed to sepsis with a sequential organ failure assessment score of 7, necessitating intensive care for several days.